Drivers of Engagement among Full-time Faculty from Private University - et.al, Gladys T. Tumbali (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This study determined the drivers of engagement among full time faculty members of University of Saint Louis, one of the Private Higher Educational Institution in the Northern Philippines. The descriptive-survey method of research was employed using a validated questionnaire. The questionnaire was administered among ninety-eight (98) full-time faculty members in the University. Data was analyzed using descriptive and inferential statistics. Findings of the study revealed that the five drivers of faculty engagement which are (1) Administration and Management, (2) Workplace and Resources, (3) Compensation and Benefit, (4) Interpersonal Relationship, and (5) Achievement and Recognition, are all important factors that drive faculty to engage themselves in their jobs. Furthermore, results showed that Compensation and Benefits was found to be the most significant driver of faculty engagement, followed by Achievement and Recognition then Administration and Management. Meanwhile, Workplace and Resources as drivers of faculty engagement was found to be less important. Furthermore, results showed that the drivers of engagement among faculty vary by department and by the highest educational attainment